PENGEMBANGAN E-LKPD MUATAN HOTS BERBASIS QUIZIZ MATERI TUMBUHAN SUMBER KEHIDUPAN DI BUMI - wistiawati lasoma; Andi Nurwati S.S; Zohrawaty Hiola (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
This study aims to develop Quizizz-based E-LKPD containing Higher Order Thinking Skills (HOTS) on the material of Plants as Sources of Life on Earth for fourth-grade elementary school students. This study uses the Research and Development (R&D) method with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The instruments used are validation sheets from material experts, media experts, and student response questionnaires. The results of the study show that the developed E-LKPD obtained the category of Feasibility of Quizizz-Based Student Worksheets on the Material of Plants as Sources of Life on Earth for Grade IV at SD Negeri 21 Limboto in the category of "Very Feasible". This was obtained from the results of the media expert validation which obtained a percentage of 90% or categorized as "Very Feasible", the results of the material expert validation obtained a percentage of 95% or categorized as "Very Feasible", the HOTS item expert validation result got 87,5% and the results of the teacher response questionnaire obtained an average percentage of 90% or categorized as "Very Feasible" and the results of the student response questionnaire obtained an average percentage of 95,6% or categorized as "Very Feasible".